Analysis of the Early Determination of the Kamariah Month Perspectives of Fiqh and Astronomy - Arsyita Baiti Musfiroh; Muhammad Himmatur Riza (Islamic Astronomy Department, Sharia and Law Faculty, 2022)
The initial determination of the lunar month in Indonesia is carried out by the Ministry of Religion of the Republic of Indonesia as a government representative, with the criteria currently used being a minimum of 2o height of the new moon, 3o of elongation and 8 hours of the new moon's age. Astronomers doubt the results of the sighting without visuals from the new moon, especially when the new moon is too low, while jurists hold on to the testimony of the explorer even though there are no visual results. One of the supporting factors for the visibility of the new moon is the weather. Therefore the author formulates the problem, namely how to determine the beginning of the lunar month according to the Indonesian Ministry of Religion and analysis according to fiqh and astronomy with the study of the Decree of the Minister of Religion (KMA) regarding the determination of the beginning of Ramadan, Shawwal and Zulhijah 1435 H/ 2014 M – 1440 H/ 2019 M. This research includes a qualitative research library. The primary data source for this research is the Decree of the Minister of Religion of the Republic of Indonesia (1 Ramadan, Shawwal and Dzulhijjah) in 1381 H -1440 H / 1962 AD - 2019 AD issued by the Directorate General of Islamic Community Guidance, Ministry of Religion of the Republic of Indonesia, while secondary data sources were obtained from documents , reports, manuscripts and technical instructions that support primary data. The determination of the beginning of the lunar month carried out by the Ministry of Religion of the Republic of Indonesia is one of the government's ijtihad carried out to unite Muslims in Indonesia, the determination through an isbat meeting based on the results of reckoning and verification of the rukyatul hilal which is carried out throughout Indonesia. In fiqh terms, the determination made by the government is in accordance with fiqh principles, including hukm al-hakim ilzan wa yarfa'u al khilaf, tasharruf al-imam 'ala raiyatih manuthun bi al mashlahah, and yattabi' al mashlahah ar raajihah. Astronomically, weather factors such as air temperature, air humidity, rainfall, wind speed and direction support the sighting of the new moon during the sighting.